The relationship between a Psychosocial Care Center and the families of users of the service: family members' perception (Research, Society and Development, 2020)
The objective was to describe the relationship between workers in a Psychosocial Care Center and the family of users of this service, from the perspective of family members. It is a qualitative, exploratory-descriptive research, carried out in a Psychosocial Care Center. Five main family caregivers participated, based on semi-structured interviews, carried out from October to November 2018. Data analysis was performed using the Thematic Content Analysis technique. The analysis resulted in two thematic categories: The construction of family - service bonds; and The family, the user and the benefits of the Psychosocial Care Center. Among the aspects mentioned by the interviewees, a relationship permeated by the bonds built was highlighted. Strategies that enable the construction of bonds with the service were identified in the reports of the main caregivers, which are, the welcoming, the qualified listening during the service, the opportunity to insert family members in the development of therapeutic workshops and meetings with the team and meeting the demands of caregivers, the active search and the realization of the family group. Furthermore, the relationship was built based on dialogue, and based on welcoming, qualified listening and establishing a bond with the family.